THE A Comparative Review on Allium Sativum and Phyllanthus Emblica - Raj, Mukut; Vyas, Girish Kumar; Sharma, Shailesh; Bishnoi, Hansraj (Asian Journal of Pharmaceutical Research and Development, 2022)
Allium sativum and Phyllanthus emblica have the ability to treat a variety of disorders through diverse formulations. The goal of this comparative analysis is to assess the extractive properties of both plants in various solvents based on their polarity. I’ve noticed that ethanol has a high potential for extracting the API from the crude medicine, which may be emblica or sativum. As a result, additional assessment and research will be conducted with the consideration of plant potential and extractive production. This review article provides information about these plants, their common names, and their diverse activities in relation to various ailments.